Managing the Accounting Information System for School Operational Aid Fund Receipts and Expenditures: Strengthening Internal Control at Public Junior High School 2 Sampit - Ananda, Hendi Diva; Putri, Eskasari (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The purpose of this research is to understand the Accounting Information System for the receipts and expenditures of BOS funds as an internal control tool at SMP N 2 Sampit. The research method used in this study is a qualitative descriptive approach. The informants in this study are the school principal and teachers of SMP N 2 Sampit. Data collection techniques include observation and interviews, while data analysis is conducted using qualitative descriptive analysis following Miles and Huberman's theory, which involves three steps: data reduction, data presentation, and drawing conclusions or verification. Triangulation techniques are employed to verify the reliability of the collected data or information. The results of this research indicate that the implementation of the Accounting Information System for the receipts and expenditures of BOS funds at SMP N 2 Sampit has been successful. Internal control over the receipts and expenditures of BOS funds at SMP N 2 Sampit has been effective. Additionally, the Accounting Information System for the receipts and expenditures of BOS funds at SMP N 2 Sampit complies with applicable regulations.